Desarrollo profesional hacia el “funcional testing” y análisis del negocio - Quispe Casas, Jesus David (2023)
Being graduated from Lima University has allowed me a group of experiences as well at work and personal, that I will consider as “priceless”. For every role and job position that I had to do, I was gathering a set of abilities and knowledgement, necessary for such a role and other functions according to the confidence earned. Along these years, my develop in certain areas and positions, as analyst developer, system consulting, functional and software quality control, software engineer level 1 and finally Testing Team Leader, also allowed me acquire not only technical skills but also “soft skills”, very important because along with the technical ones may guide through communication, empathy, confidence and others to get professional improvements, promotions, bonus and recognitions for performance, productivity and goals achievements. After achieving the expected promotion for being the Testing Team Leader, goals achievement and tasks accomplishment and leading and managing human resources was not an easy task, not all the people have the same motivation, commitment in accomplishing daily tasks. It was right there where I had to use all the soft skills for communicating, negotiating and to be the guide for our collaborators may achieve their goals in benefit of the project and company. Finally, graduating from the System Engineering Faculty from University of Lima provides you the tools and opportunities that allow you to grow and acquire the necessary skills to achieve the success that we wish.